Pravice vs toleranca. Mentalitetna inkongruentnost - Kramberger, Taja (Šolsko polje, 2010)
In the first section of this paper we examine - by means of historical anthropology and discursive analysis - the context of individual articles in the Declaration of the Rights of Man and the Citizen from 1789, while in its second section we turn out critical attention to the official Slovenian translation of Article X. We try to show the basic distinction between the regime of tolerance (religious tolerance that later evolved into and was replaced by civic tolerance) and the regime of rights (rights of men and citizens). It is argued that the social mechanisms of tolerance are almost always connected to the hierarchical social structures, and by that the subject who possesses the tolerance by his own will and by the strategies of power gives permission and grants something to the subject who has neither thepower nor the right to do it. It was possible for the Declaration of the Rights of Man and the Citizen to bring about a new confi guration of social relations once it was no longer used within the context of religious dispositive deployment and applied instead to a completely diff erent social and epistemic (discursive) order.
Keywords: toleranca; Tolerance; Deklaracija o pravicah človeka in državljana; prevodi; prilastitev; mentaliteta; človekove pravice; human rights